Firm Performance in India : Does Sustainability Reporting Matter? - M. C., Minimol; K. V., Akhila; Kavya, N. P. (Indian Journal of Finance, 2025)
Purpose : The current study intended to explore the relationship between sustainability reporting practices and firms’ financial, operational, and market-oriented performance. It also aimed to understand whether the quality of sustainable reporting positively influenced firm performance. Methodology : We used Indian firm-level data to analyze the effect of sustainability reporting on firm performance. Using dynamic panel data models and panel quantile regression, we developed three models to examine the relationship between sustainability reporting and firm performance. We have used 7,000 data points from 100 different companies over 7 years, from 2017 to 2023. Data were analyzed using STATA software. Findings : The results demonstrated a significant positive relationship between sustainability reporting, quality of sustainability reporting, and firm performance according to the financial, operational, and market-oriented performance models. Since the return on assets is an accounting-oriented metric that indicates a company’s short-run financial performance, we assumed that there was a positive relationship between sustainability reporting and the short-term performance of firms. Practical Implications : Since customers and investors at large are now moving toward sustainable companies and investments, an effort on the part of companies to disclose their sustainability efforts had a positive effect on their return on assets, return on equity, and Tobin’s Q. Originality : Our results indicated that sustainability reporting positively impacted the accounting, operational, and market-oriented performance matrices of listed companies.